PELATIHAN MELAKUKAN NEED ASESMENT SISWA SECARA ONLINE PADA MASA NEW NORMAL COVID-19 - Donal Donal; R. Arlizon; Rosmawati; Munawir (Politeknik Negeri Sriwijaya, 2022)
This service activity aims that training participants can make and carry out student needs assessments during the pandemic well and can do it online without having to enter class or meet students in person, thereby minimizing the spread of covid-19 and increasing professional skills as teachers in schools. This activity is carried out online or online. The methods of implementing community service activities are lectures, demonstrations and exercises to make student assessment instruments need and train teachers to online the instruments that have been made using the Google Form application. The target of this training activity for making needs assessment instruments is junior high school, high school and vocational school teachers in Kampar Regency. Based on service activities, it can be concluded; Increased knowledge of guidance and counseling teachers in Kampar Regency in Conducting Online Student Need Assessments at schools.